2020
DOI: 10.1108/ijssp-07-2020-0358
|View full text |Cite
|
Sign up to set email alerts
|

Providing a foundation for decent work and adequate income during health and economic crises: constitutional approaches in 193 countries

Abstract: PurposeAs coronavirus disease 2019 (COVID-19) spreads globally, the economic and health consequences are disproportionately affecting marginalized workers. However, countries' existing labor and social security laws often exclude the most vulnerable workers from coverage, exacerbating existing inequalities. Guaranteeing the rights to adequate income even when ill, decent working conditions and nondiscrimination in constitutions may provide a foundation for protecting rights universally, safeguarding against co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…Although there are some connections between these other words, the most relevant links are those between these words and "COVID-19", showing a clear connection between these themes. The cluster content follows the authors' statement [11,12]. Throughout the pandemic, many companies' bankruptcies, job reductions, layoffs, and, consequently, people started to glimpse informal employment as a form of survival [13].…”
Section: Introduction 32mentioning
confidence: 90%
See 2 more Smart Citations
“…Although there are some connections between these other words, the most relevant links are those between these words and "COVID-19", showing a clear connection between these themes. The cluster content follows the authors' statement [11,12]. Throughout the pandemic, many companies' bankruptcies, job reductions, layoffs, and, consequently, people started to glimpse informal employment as a form of survival [13].…”
Section: Introduction 32mentioning
confidence: 90%
“…However, SDGs are broader and present a more detailed scope 43 than the Millennium Development Goals. In addi-44 tion, the SDGs highlight the possibility that different actors establish partnerships allowing greater mobilisation of data, resources and capacity development and technologies, aiming to achieve the mentioned debts while the prices of essential products increased 88 and reduced exports and imports [11,12]. Rocha 89 et al [13] argued that informal work was an alter-90 native for families income and survival in several regions.…”
Section: Introduction 32mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, even though there are some studies relating elements of Decent Work to SWB, it was not found a study that encompasses the different elements that makeup Decent Work in its SWB relationship (Cerci and Dumludag, 2019;Karani and Mehta, 2022;Lambert et al, 2021;Valencia et al, 2022). Elements such as workleisure balance, income level, work informality and critical conditions will constitute a way to identify whether the Decent Work construct influences employees' level of SWB (Rashmi and Kataria, 2021;Sprague et al, 2020). Thus, the present study aims to explore which components of Decent Work, according to the definitions of Rashmi and Kataria (2021) and Sprague et al (2020), have a significant association with Subjective Well-Being.…”
Section: Decent Work and Subjective Well-beingmentioning
confidence: 99%
“…Decent Work is a multidimensional concept promoted by the International Labour Organization (ILO), used as a reference to establish minimum working conditions in sufficient quantity and quality; it also implies work with freedom, equity, justice and equality (ILO, 1999). Decent Work includes a salary that allows workers and their families a decent life, safe working conditions, access to social security, free time and rest (Rashmi and Kataria, 2021;Sprague et al, 2020). Decent Work is the eighth sustainable development goal of the United Nations and is an essential part of the Agenda of the ILO.…”
Section: Introductionmentioning
confidence: 99%